O impacto da digitalização nos procedimentos de higienização em restaurantes: estudo de caso do desenvolvimento de aplicativo low-code para registro de limpeza - Lima, Isabella Santiago (2025)
Good practices in food services, especially the sanitization of facilities, equipment, furniture,and utensils, are fundamental to guaranteeing the quality and safety of the meals produced. Allied to this, digitalization, accelerated by the COVID-19 pandemic, can help facilitate the recording of these activities in a more agile way. Therefore, this study aimed to develop a low- code cleaning record application for restaurants, to evaluate and analyze, through a literature review, good practices in food services, the sanitation of facilities, equipment, furniture, and utensils, and the importance of digitalization for this sector. The methodology used was divided into two parts: a literature review and the development of the application. The first was carried out by researching, reading, and selecting articles, publications in periodicals, books, ANVISA Resolution RDC No. 216 of 2004, as well as recent documentation and articles from Microsoft, with the selection criterion being the limitation of time, with emphasis on the last five years. The application, in turn, was developed in sequential stages: gathering the information needed for registration, creating lists in SharePoint, designing the screen layout in Figma, and developing the functionalities in Power Apps. The screens developed, in turn, were as follows: home screen, responsible for welcoming the user and directing them to start the registration; navigation menu, containing buttons to direct them to the other screens in the application; registration, in which the cleaning information is filled in; history, to search for previous registrations quickly and accurately; schedule, containing the cleaning frequencies for each surface, making it possible to search in case of doubt and set up the cleaning schedule; calendar, essential for planning the next cleanings; and adding events, to add future cleanings. In light of the study, it was concluded that the application could provide greater productivity for employees, minimizing errors in filling out the application, speeding up the search for specific information, reducing the use of paper, reducing costs, allowing for a more secure record of the cleaning carried out and, consequently, greater quality and safety of the food prepared, being considered an advance in relation to the forms of cleaning records on printed control sheets.